Volume defects of crystal structure in alkali halide crystals grown from melt by continuous automated method - Goriletsky, V.I.; Tymoshenko, M.M.; Vasyliev, V.V.; Ilyashenko, T.O. (Functional Materials, 2008)
The types of crystal structure defects (CSD) and the formation causes thereof in Csl(Na), Csl(TI), and Nal(TI) crystals of 290 to 520 mm diameter are considered. It has been shown that the CSD of impurity capture type are formed mainly due to disturbed crystallization equilibrium caused by a sharp change in the heat transfer from the growing crystal to water-cooled growth furnace walls. In the ROST units of two generations differing in size and thus in the growing crystal dimensions, this occurs at the height of the crystal cylindrical part of 50 and 70 mm, respectively. The CSD in the form of a local deterioration of the crystal transparence can arise at any crystal height after its exit from the crucible. Those are due to local changes in the crystallization front (CF) shape caused by the temperature variation rate of the controlling heater exceeding the permissible one. This process is accompanied by the crystal diameter increase and acceleration of the crystal linear growth at the CF. Розглядаються типи дефектів кристалічної структури (ДКС) та причини їх утворення у сцинтиляційних кристалах Csl(Na), Csl(TI) та NаІ(ТІ) діаметром від 290 до 520 мм. Показано, що головною причиною утворення ДКС типу захоплень сторонніх домішок є порушення умов рівноважної кристалізації, що спричиняється різкою зміною теплоперенесення від кристала, що росте, до стінок вирощувальної печі, що водоохолоджуються. Для установок серії "РОСТ" двох поколінь, що відрізняються габаритами і, відповідно, розмірами кристалів, що ростуть, це відбувається на висоті циліндричної частини кристала відповідно 50 та 70 мм. ДКС у вигляді локального погіршення прозорості кристала можуть утворюватися на будь-якій висоті кристала після його виходу з тигля. Причиною їх утворення є локальна зміна форми фронту кристалізації (ФК), зумовлене перевищенням граничної швидкості зміни температури на нагрівачі, що регулюється. Цей процес супроводжується прирощенням діаметра кристала та збільшенням лінійної швидкості росту на ФК. Рассматриваются виды дефектов кристаллической структуры (ДКС) и причины их образования в сцинтилляционных кристаллах Csl(Na), Csl(ТI) и Nal(ТJ) диаметром от 290 до 520 мм. Показано, что основной причиной образования ДКС типа захватов посторонних примесей является нарушение условий равновесной кристаллизации, обусловленное резким изменением теплопереноса от растущего кристалла к водоохлаждаемым стенкам ростовой печи. Для установок серии "РОСТ" двух поколений, отличающихся габаритами и, соответственно, размерами выращиваемых кристаллов, это происходит на высоте цилиндрической части кристалла 50 и 70 мм, соответственно. ДКС в виде локального ухудшения прозрачности кристалла могут образовываться на любой высоте кристалла после выхода его из тигля. Причиной их образования является локальное изменение формы фронта кристаллизации (ФК), обусловленное превышением допустимой скорости изменения температуры на регулирующем нагревателе. Этот процесс сопровождается приращением диаметра кристалла и увеличением линейной скорости роста на ФК.